ENGLISH LECTURER’S STRATEGIES IN TEACHING SPEAKING DURING COVID-19 PANDEMIC - Wilany Alya Dwi Pratiwi; Dadang Solihat; Endang Darsih (Indonesian Journal of Learning and Instruction)
The objective of this research was to find out an English Lecturer’ strategies in teaching speaking during COVID-19 pandemic and to know students’ attitude toward the implementation of the strategies. This study applied a qualitative method with case study design, the subject of the research was an English lecturer who teaching speaking course and five students from English education department of Kuningan University. The data was collected by using an observation checklist and interview. The result of the research revealed that there are 7 strategies used by the lecturer in teaching speaking. There are: 1) Voice Note WhatsApp, 2) Video Conference, 3) Learning Video, 4) Podcast, 5) Video Assignment, 6) Structure Task / Structure Project and 7) ELSASpeak Application. From 7 strategies only a few strategies are considered quite effective. Keywords: English lecturer strategies; teaching strategies